2022
DOI: 10.3389/fimmu.2022.987227
|View full text |Cite
|
Sign up to set email alerts
|

Angioimmunoblastic T-cell lymphoma with predominant CD8+ tumor-infiltrating T-cells is a distinct immune pattern with an immunosuppressive microenvironment

Abstract: BackgroundAngioimmunoblastic T-cell lymphoma (AITL) has a rich tumor microenvironment (TME) that typically harbors plenty of CD4+tumor infiltrating lymphocytes, (TIL)-T-cells (so called common AITL). Nonetheless, AITL with large numbers of CD8+TIL-Ts that outnumber CD4+cells have been observed (CD8-predominant AITL). However, detailed comparison of CD8-predominant AITL and common AITL are still lacking.MethodsWe compared clinicopathological features, TIL subsets, TME T cell receptor-β (TRB), and immunoglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…CD8 + TILs can exert anti-tumor functions ( 11 ) through several pathways such as the release of GZMA and GZMB, Fas-Fas ligand pathway-mediated apoptosis ( 14 , 15 ), and secretion of inflammatory cytokines like IFN-γ ( 16 ) and TNF-α ( 17 ). We previously found that an increase in CD8 + TILs had a negative impact on the prognosis of AITL at the protein level ( 3 , 4 ), and hypothesized that CD8 + TILs are exhausted in AITL. Intriguingly, Pritchett et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD8 + TILs can exert anti-tumor functions ( 11 ) through several pathways such as the release of GZMA and GZMB, Fas-Fas ligand pathway-mediated apoptosis ( 14 , 15 ), and secretion of inflammatory cytokines like IFN-γ ( 16 ) and TNF-α ( 17 ). We previously found that an increase in CD8 + TILs had a negative impact on the prognosis of AITL at the protein level ( 3 , 4 ), and hypothesized that CD8 + TILs are exhausted in AITL. Intriguingly, Pritchett et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there were obvious deficiencies in the biological function of CD8 + TILs in the high CTL group, characterized by the dysregulated expression of genes related to metabolism, mitochondria, and effector function in CD8 + TILs, suggesting a disturbance in normal metabolic processes ( 27 ), mitochondrial dysfunction, and deficiency in energetic adaptations ( 28 , 29 ). Further, several chemokines were enriched in the high-CTL group, which could recruit M2 macrophages ( 30 ) and Tregs ( 31 ), thereby enhancing immune suppression in the TME ( 4 ) and aggravating the exhaustion of CD8 + TILs. In summary, exhausted CD8 + TILs in the high CTL group exhibited abnormal biological changes in addition to high IC expression, suggesting a more severe degree of CD8 + TILs exhaustion in the high CTL group than in the low CTL group, eventually resulting in tumor proliferation ( 32 ) and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…278 Accordingly, the survival and proliferation of these malignant T FH cells are highly dependent on their collaboration with GCB cells. 279 Intriguingly, TET2-mutated GCB cells were discovered in the LME, which undergo independent clonal evolution and support the growth of T FH -like tumor cells via the CD40-CD40LG axis in ACH-related TFH lymphoma, angioimmunoblastic type. 96 These genetically aberrant B-cells exhibit a global shift in phenotypes, marked by a decreased expression of CD73 and CXCR5, which are critical molecules for B-cell homing and germinal center formation.…”
Section: Extrinsic Pathogenic Mechanisms and Targeted Therapies Micro...mentioning
confidence: 99%
“…62,63 Reactive CD8 + cells are variably abundant and may outnumber the CD4 + neoplastic cells. 64 The large B-cell immunoblasts are positive for CD20, PAX5 and CD79a, often CD30, and may also sometimes co-express CD15. They are usually, but not always, infected by EBV (positive for EBV-encoded RNA [EBER] and latent membrane protein 1 [LMP-1]).…”
Section: Follicular Helper T-cell Lymphomamentioning
confidence: 99%